Development of Mathematical Cognitive Test Instruments on Fraction Materials for Elementary School Students Based on Idea Exploration Ability - Fitriya, Yeni; Kurniawan, Hendra Listya; Latif, Ardiyan (Department of Mathematics Education Program IPI Garut, 2023)
Eksplorasi ide sebagai bagian dari disposisi matematis memiliki peran penting bagi siswa. Dengan kemampuan eksplorasi ide, siswa akan mampu memecahkan soal matematika secara mandiri dan kreatif untuk mendukung keberhasilan pembelajaran matematika. Namun berdasarkan studi pendahuluan diketahui kemampuan eksplorasi ide siswa dalam menyelesaikan soal cerita materi pecahan masih rendah. Penelitian ini bertujuan mengembangkan instrument tes kognitif dengan membuktikan validitas dan reliabilitas konstruk instrumen tes eksplorasi ide materi pecahan di sekolah dasar. Metode penelitian ini adalah kuantitatif secara cross sectional dengan 307 siswa sebagai subjek penelitian. Analisis data menggunakan analisis faktor konfirmasi dengan software SPSS 26 dan Lisrel 8.80 untuk mengetahui nilai indeks daya beda dan nilai muatan faktor yang kemudian digunakan untuk menemukan nilai korelasi antar dimensi (AVE), validitas konstruk dan reliabilitas instrumen. Hasil penelitian menunjukan terdapat 12 butir soal valid secara konstruk dan reliabel. Penelitian ini memberikan implikasi dan rekomendasi dalam penggunaan instrument tes berbasis eksplorasi ide di sekolah dasar. Exploration of ideas as part of a mathematical disposition is essential for students. With the ability to explore ideas, students can solve math problems independently and creatively to support the success of learning mathematics. However, based on a preliminary study shows that student's ability to explore ideas in solving word problems on fractions is still low. This study aims to develop by proving the construct validity and reliability of the exploratory test instrument for ideas on fractional material in elementary schools. The method in this study was quantitative with a cross-sectional method with 307 students as research subjects. Data analysis was carried out by confirming factor analysis using SPSS 26 and Lisrel 8.80 software to determine the value of the differential index and factor loading values which can then be used to find the inter-dimensional correlation (AVE) values, construct validity, and instrument reliability. Of the 35 items, 17 questions have high discriminatory power to be analyzed using Lisrel 8.80. The results showed that 12 items were stated to be constructively valid and reliable. This study provides implications and recommendations for using test instruments based on idea exploration in elementary schools.